Specificity of spiders among fear- and disgust-eliciting arthropods: Spiders are special, but phobics not so much - Landová, Eva; Janovcová, Markéta; Štolhoferová, Iveta; Rádlová, Silvie; Frýdlová, Petra; Sedláčková, Kristýna; Frynta, Daniel (PloS one, 2021)
To investigate a specificity of spiders as a prototypical fear- and disgust-eliciting stimuli, we conducted an online experiment. The respondents rated images of 25 spiders, 12 non-spider chelicerates, and 10 other arthropods on a fear and disgust 7-point scale. The evaluation of 968 Central European respondents confirmed the specificity of spiders among fear- and disgust-eliciting arthropods and supported the notion of spiders as a cognitive category. We delineated this category as covering extant spider species as well as some other chelicerates bearing a physical resemblance to spiders, mainly whip spiders and camel spiders. We suggested calling this category the spider-like cognitive category. We discussed evolutionary roots of the spider-like category and concluded that its roots should be sought in fear, with disgust being secondary of the two emotions. We suggested other chelicerates, e.g., scorpions, might have been important in formation and fixation of the spider-like category. Further, we investigated an effect of respondent's sensitivity to a specific fear of spiders on evaluation of the stimuli. We found that suspected phobic respondents were in their rating nearly identical to those with only high fear of spiders and similar to those with only moderate fear of spiders. We concluded that results based on healthy respondents with elevated fear should also be considered relevant for arachnophobia research.
Keywords: Young Adult; Male; emoce; strach; mladý dospělý; Emotions; Adult; Aged; dospělí; členovci; mužské pohlaví; senioři; Fear; Spiders; Arthropods; testování osobnosti; Disgust; Animals; lidé; ženské pohlaví; pavouci; Humans; zvířata; odpor; Female; Personality Assessment; lidé středního věku; Middle Aged